Inventarisasi Jenis-jenis Mamalia di Hutan Pendidikan dan Penelitian Biologi (HPPB) Universitas Andalas dengan Menggunakan Camera Trap - - Junaidi; - Rizaldi; Wilson Novarino (Universitas Andalas, 2012)
An inventory of mammalian species at The Biological Education and Research Forest (HPPB) Andalas University was conducted from November 2011 to March 2012. We used six camera traps operated along forest paths where those predicted as regular tracks of the animals. We successfully identified ten species of mammals in which they belong to ten families and six orders. Those identified species were Hylomys suillus, Macaca nemestrina, Manis javanicus, Lariscus insignis, Hystrix brachyura, Ursus malayanus, Panthera tigris sumatrae, Sus scrofa, Tragulus javanicus and Muntiacus muntjak. The two species, Lariscus insignis and Hylomys suillus were new record from this area.Keywords: mammals, camera trap, Biological Education and Research Forest